Coralline Algae in a Changing Mediterranean Sea: How Can We Predict Their Future, if We Do Not Know Their Present? - Rindi, Fabio; Braga, Juan C.; Martin, Sophie; Peña, Viviana; Le Gall, Line; Caragnano, Annalisa; Aguirre, Julio (Frontiers in Marine Science, 2019)
In this review we assess the state of knowledge for the coralline algae of the Mediterranean Sea, a group of calcareous seaweeds imperfectly known and considered highly vulnerable to long-term climate change. Corallines have occurred in the Mediterranean area for approximately 140 My and are well represented in the subsequent fossil record; for some species currently common the fossil documentation dates back to the Oligocene, with a major role in the sedimentary record of some areas. Some Mediterranean corallines are key ecosystem engineers that produce or consolidate biogenic habitats (e.g., coralligenous concretions, Lithophyllum byssoides rims, rims of articulated corallines, maerl/rhodolith beds). Although bioconstructions built by corallines exist virtually in every sea, in the Mediterranean they reach a particularly high spatial and bathymetric extent (coralligenous concretions alone are estimated to exceed 2,700 km2 in surface). Overall, composition, dynamics and responses to human disturbances of coralline-dominated communities have been well studied; except for a few species, however, the biology of Mediterranean corallines is poorly known. In terms of diversity, 60 species of corallines are currently reported from the Mediterranean. This number, however, is based on morphological assessments and recent studies incorporating molecular data suggest that the correct estimate is probably much higher. The responses of Mediterranean corallines to climate change have been the subject of several recent studies that documented their tolerance/sensitivity to elevated temperatures and pCO2. These investigations have focused on a few species and should be extended to a wider taxonomic set. Phylogeography, genomics, transcriptomics, and associated microbiomes are fields in which the information for Mediterranean corallines is very limited. We suggest that future work on Mediterranean corallines should be based on a multidisciplinary perspective combining different approaches, and that it should consist of large-scale efforts by scientists based both in western and eastern Mediterranean areas.